PENERAPAN MEDIA PEMBELAJARAN QUIZIZZ PADA ELEMEN UTILITAS BANGUNAN TERHADAP HASIL BELAJAR SISWA KELAS XI KGS DI SMK - Natasya Vania Rahmawati; Hendra Wahyu Cahyaka (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2026)
This investigation was engineered to mathematically analyze the variance in students' learning outcomes and map their perceptual responses toward the integration of Quizizz-based instructional media as opposed to conventional PowerPoint (PPT) platforms. The study was anchored on the pedagogical imperative of incorporating interactive digital toolkits to stimulate student engagement and transmute abstract vocational contents into highly consumable and engaging structures. Methodologically, a quantitative paradigm was deployed utilizing a quasi-experimental design. The research subjects were stratified into two distinct observational cohorts within the 11th-grade Building Construction and Sanitation (KGS) department at SMK Negeri 5 Surabaya: the control group operating via PowerPoint frameworks and the experimental group subjected to the Quizizz intervention. Academic performance vectors were synthesized using pretest and posttest instruments, whereas students' psychological acceptance of the respective media was captured through structured questionnaires. The empirical outcomes demonstrate a statistically significant disparity in learning outcomes between the two treatment groups. Numerically, the experimental cohort's mean score expanded from a baseline of 66.3 to 86.6, whereas the control cohort's mean score shifted from 61.4 to 83.2. The inferential t-test calculation yielded a significance coefficient of 0.022 ($< 0.05$), validating the superior efficacy of the gamified platform over traditional delivery modes. Furthermore, the perceptual matrix indicated that 80% of students' cumulative evaluations regarding Quizizz fell squarely into the "very good" category, signaling an intensely positive reception toward classroom gamification. Consequently, this digital tool stands as a highly viable instructional alternative to maximize evaluation metrics and accelerate conceptual mastery within vocational secondary educational ecosystems. ABSTRAK Investigasi ini diorientasikan untuk menguji komparasi capaian hasil belajar peserta didik sekaligus memetakan kecenderungan respons siswa terhadap pengintegrasian media instruksional berbasis Quizizz dibandingkan dengan pemanfaatan PowerPoint (PPT). Landasan empiris riset ini berpijak pada urgensi optimalisasi perangkat digital interaktif guna mengikis kepasifan kelas, mengeskalasi keterikatan (engagement) siswa, serta menyajikan konten teknik yang lebih berkarakter visual dan aplikatif. Pendekatan kuantitatif diintegrasikan dalam penelitian ini melalui penerapan rancangan eksperimen semu (quasi-experimental design). Komunitas subjek dipecah ke dalam dua klaster observasi: kelompok kontrol yang mengadopsi PowerPoint serta kelompok eksperimen yang diintervensi menggunakan platform Quizizz pada siswa kelas XI kompetensi keahlian Konstruksi Gedung dan Sanitasi (KGS) di SMK Negeri 5 Surabaya. Pengumpulan data performa akademis dihimpun via instrumen pretest dan posttest, sedangkan dinamika psikologis siswa terhadap media dijaring lewat penyebaran angket kuisioner. Keluaran riset mengonfirmasi adanya disparitas secara signifikan pada grafik hasil belajar antara intervensi kelompok eksperimen dan kelompok kontrol. Secara numerik, rerata skor pada kelompok eksperimen melejit dari posisi awal 66,3 menuju angka 86,6; sementara itu, rerata skor pada kelas kontrol bergerak dari basis data 61,4 menjadi 83,2. Hasil komputasi uji-t menghasilkan koefisien signifikansi sebesar 0,022 ($< 0,05$), yang memvalidasi keunggulan efikasi platform gamifikasi tersebut. Di samping itu, matriks data persepsi merekam bahwa 80% akumulasi respons siswa terhadap aplikasi Quizizz masuk dalam kualifikasi "sangat baik". Indikator ini membuktikan hadirnya akseptasi yang sangat positif terhadap digitalisasi permainan kuis di ruang kelas vokasional.